Biomechanical study of two-level oblique lumbar interbody fusion with different types of lateral instrumentation: a finite element analysis - Zhong, Yuan; Wang, Yujie; Zhou, Hong; Wang, Yudong; Gan, Ziying; Qu, Yimeng; Hua, Runjia; Chen, Zhaowei; Chu, Genglei; Liu, Yijie; Jiang, Weimin (Frontiers in Medicine, 2023)
Objective The aim of this study was to verify the biomechanical properties of a newly designed angulated lateral plate (mini-LP) suited for two-level oblique lumbar interbody fusion (OLIF). The mini-LP is placed through the lateral ante-psoas surgical corridor, which reduces the operative time and complications associated with prolonged anesthesia and placement in the prone position. Methods A three-dimensional nonlinear finite element (FE) model of an intact L1–L5 lumbar spine was constructed and validated. The intact model was modified to generate a two-level OLIF surgery model augmented with three types of lateral fixation (stand-alone, SA; lateral rod screw, LRS; miniature lateral plate, mini-LP); the operative segments were L2–L3 and L3–L4. By applying a 500 N follower load and 7.5 Nm directional moment (flexion-extension, lateral bending, and axial rotation), all models were used to simulate human spine movement. Then, we extracted the range of motion (ROM), peak contact force of the bony endplate (PCFBE), peak equivalent stress of the cage (PESC), peak equivalent stress of fixation (PESF), and stress contour plots. Results When compared with the intact model, the SA model achieved the least reduction in ROM to surgical segments in all motions. The ROM of the mini-LP model was slightly smaller than that of the LRS model. There were no significant differences in surgical segments (L1–L2, L4–L5) between all surgical models and the intact model. The PCFBE and PESC of the LRS and the mini-LP fixation models were lower than those of the SA model. However, the differences in PCFBE or PESC between the LRS- and mini-LP-based models were not significant. The fixation stress of the LRS- and mini-LP-based models was significantly lower than the yield strength under all loading conditions. In addition, the variances in the PESF in the LRS- and mini-LP-based models were not obvious. Conclusion Our biomechanical FE analysis indicated that LRS or mini-LP fixation can both provide adequate biomechanical stability for two-level OLIF through a single incision. The newly designed mini-LP model seemed to be superior in installation convenience, and equally good outcomes were achieved with both LRS and mini-LP for two-level OLIF.